2013
DOI: 10.1021/am404042r
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Investigation on the Interactions between Magnetic Nanoparticles and Cell Membrane Models

Abstract: The understanding of the interactions between small molecules and magnetic nanoparticles is of great importance for many areas of bioapplications. Although a large array of studies in this area have been performed, aspects involving the interaction of magnetic nanoparticles with phospholipids monolayers, which can better mimic biological membranes, have not yet been clarified. This study was aimed at investigating the interactions between Langmuir films of dipalmitoyl phosphatidylglycerol and dipalmitoyl phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…18,19 Until today, the emergence of several biomimetic model membranes based on lipid nanosystems and biophysical techniques to study and characterize drug-membrane interactions have resulted in new concerns about how a drug influences membrane properties and vice-versa. [19][20][21][22][23][24][25][26][27][28][29][30] In our previous works, as well as in other studies, it is reported the correlations between the biological action and cytotoxicity of drugs and their biophysical effects in biomimetic membranes, eg by altering lipid membrane packing, decreasing lipid membrane transition temperatures or disturbing cooperativity of lipid unit cells, with consequent membrane biophysical impairment. 21,[26][27][28]31,32 Additionally, several interesting reports 19,20,[33][34][35][36][37] highlighted the importance of biomimetic models based on lipid nanosystems (liposomes, monolayers and supported lipid bilayers) to acquire molecular and functional information.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…18,19 Until today, the emergence of several biomimetic model membranes based on lipid nanosystems and biophysical techniques to study and characterize drug-membrane interactions have resulted in new concerns about how a drug influences membrane properties and vice-versa. [19][20][21][22][23][24][25][26][27][28][29][30] In our previous works, as well as in other studies, it is reported the correlations between the biological action and cytotoxicity of drugs and their biophysical effects in biomimetic membranes, eg by altering lipid membrane packing, decreasing lipid membrane transition temperatures or disturbing cooperativity of lipid unit cells, with consequent membrane biophysical impairment. 21,[26][27][28]31,32 Additionally, several interesting reports 19,20,[33][34][35][36][37] highlighted the importance of biomimetic models based on lipid nanosystems (liposomes, monolayers and supported lipid bilayers) to acquire molecular and functional information.…”
Section: Introductionmentioning
confidence: 85%
“…This information can also assist to the design of new chemical entities with improved efficacy and reduced toxicity, 19,34,37 or even to understand the interaction of drug delivery nanosystems with biomembranes. 30,34,38,39 Therefore, in this study, the interaction of AntiOxCIN 3 with the most relevant biointerfaces was studied and characterized allying in silico descriptors with different in vitro biophysical methods and biomimetic model systems to predict its biodistribution behavior. In order to mimic the journey of AntiOxCIN 3 in the body after oral administration, four different biomimetic interface models were considered: (i) micelles of intestinal biliary salts; (ii) human serum albumin (HSA); (iii) lipid nanosystems (lipid vesicles and lipid bilayers) used as membrane models, which are composed by phosphatidylcholine (PC) as the main phospholipid component of cell membranes; and (iv) lipid nanosystems (lipid vesicles) composed of lipids from the endothelial membrane of BBB mimicking this important lipid biointerface.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for the NPs/DPPC system, both types of nanoparticles are capable of interacting with the zwitterionic DPPC molecules, forming an overlayer of lipid-covered NPs on top of the DPPC film, which leads to a reduction in the area per molecule [277].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…SFG spectroscopy/microscopy has already proven to be of great interest in the study of model biointerfaces in the past [70,71]. In fact, the studies of interactions of magnetic nanoparticles [72] or AuNPs [73] with cell membrane models are performed on more or less complex interfaces made of supported lipid bilayers. Indeed, small AuNPs may interact with the cell membrane but the interaction mechanism at the nanoscale is not well understood.…”
Section: Recent Developments In Sfg Spectroscopy Of Plasmonic Matementioning
confidence: 99%